You are on page 1of 4

By Hinyu & Other Minians at Miniforum

Suggested Solution for 2009 Pure Mathematics Paper 1 2nd Edition, last updated at 00:42 on 8 October 2009

1 A B C
Let = + + where A, B and C are constants.
(2x − 1)(2x + 1)(2x + 3) 2x − 1 2x + 1 2x + 3

1 A B C
= + +
(2x − 1)(2x + 1)(2x + 3) 2x − 1 2x + 1 2x + 3
⇐⇒ 1 = A(2x + 1)(2x + 3) + B(2x − 1)(2x + 3) + C(2x − 1)(2x + 1) (∗1)

Method 1 – Find A, B and C by substitution

1 1 3
Put x = , − and − into (∗1) respectively,
2 2 2

1 = 8A 1 = −4B 1 = 8C
1 1 1
⇐⇒ A= ⇐⇒ B=− ⇐⇒ C=
8 4 8

Method 2 – Find A, B and C by comparing coefficients

From (∗1),

1 = A(2x + 1)(2x + 3) + B(2x − 1)(2x + 3) + C(2x − 1)(2x + 1)


⇐⇒ 1 = A(4x2 + 8x + 3) + B(4x2 + 4x − 3) + C(4x2 − 1)
⇐⇒ 1 = (4A + 4B + 4C)x2 + (8A + 4B)x + (3A − 3B − C)

Compare the coefficients on both sides of the above equation,



 4A
 +4B +4C = 0
8A +4B =0

3A −3B −C1 = 1

1 1 1
On solving, A = , B = − and C = .
8 4 8

1 1 1 1
∴ = − +
(2x − 1)(2x + 1)(2x + 3) 8(2x − 1) 4(2x + 1) 8(2x + 3)

n
X 1
Method 1 – Evaluate
(2k − 1)(2k + 1)(2k + 3)
k=1

–1–
By Hinyu & Other Minians at Miniforum
Suggested Solution for 2009 Pure Mathematics Paper 1 2nd Edition, last updated at 00:42 on 8 October 2009

For any positive integer n,


n n  
X 1 X 1 1 1
= − + (From (a))
(2k − 1)(2k + 1)(2k + 3) 8(2k − 1) 4(2k + 1) 8(2k + 3)
k=1 k=1
n n n
1 X 1 1X 1 1X 1
= − +
8 2k − 1 4 2k + 1 8 2k + 3
k=1 k=1 k=1
n n+1 n+2
1X 1 1 X 1 1X 1
= − + (#1)
8 2k − 1 4 2k − 1 8 2k − 1
k=1 k=2 k=3
n n 1 n+1
!
1X 1 1 X 1 X 1 X 1
= − − +
8 2k − 1 4 2k − 1 2k − 1 2k − 1
k=1 k=1 k=1 k=n+1
n 2 n+2
!
1 X 1 X 1 X 1
+ − +
8 2k − 1 2k − 1 2k − 1
k=1 k=1 k=n+1
      
1 1 1 1 1 1
=− −1 + + − 1+ + +
4 2n + 1 8 3 2n + 1 2n + 3
1 1 1
= − + (∗2)
12 8(2n + 1) 8(2n + 3)

Explanation

(#1) In the 2nd summation, k + 1 is replaced by k, so the starting and ending values of the summation indices
increase by 1.

In the 3rd summation, k + 2 is replaced by k, so the starting and ending values of the summation indices
increase by 2.

n
X 1
Method 2 – Evaluate
(2k − 1)(2k + 1)(2k + 3)
k=1

For any positive integer n,


n n  
X 1 X 1 1 1
= − + (From (a))
(2k − 1)(2k + 1)(2k + 3) 8(2k − 1) 4(2k + 1) 8(2k + 3)
k=1 k=1
n   n  
1X 1 1 1X 1 1
= − − −
8 2k − 1 2k + 1 8 2k + 1 2k + 3
k=1 k=1
n   n+1  
1X 1 1 1X 1 1
= − − − (#2)
8 2k − 1 2k + 1 8 2k − 1 2k + 1
k=1 k=2
n   " n  
1X 1 1 1 X 1 1
= − − −
8 2k − 1 2k + 1 8 2k − 1 2k + 1
k=1 k=1
1   n+1
X  1 #
X 1 1 1
− − + −
2k − 1 2k + 1 2k − 1 2k + 1
k=1 k=n+1
    
1 1 1 1
=− − 1− + −
8 3 2n + 1 2n + 3
1 1 1
= − + (∗2)
12 8(2n + 1) 8(2n + 3)

–2–
By Hinyu & Other Minians at Miniforum
Suggested Solution for 2009 Pure Mathematics Paper 1 2nd Edition, last updated at 00:42 on 8 October 2009

Explanation

(#2) In the 2nd summation, k + 1 is replaced by k, so the starting and ending values of the summation indices
increase by 1.

Take n → ∞ on both sides of (∗2),


∞  
X 1 1 1 1
= lim − +
(2k − 1)(2k + 1)(2k + 3) n→∞ 12 8(2n + 1) 8(2n + 3)
k=1
1 1 1 1 1
=− lim + lim (All limits exist.)
12 8 n→∞ 2n + 1 8 n→∞ 2n + 3
1 1 1
= − ·0+ ·0
12 8 8
1
=
12
For any positive integers m and n such that 1 < m ≤ n,
n n m−1
X 1 X 1 X 1
= −
(2k − 1)(2k + 1)(2k + 3) (2k − 1)(2k + 1)(2k + 3) (2k − 1)(2k + 1)(2k + 3)
k=m k=1 k=1
 
1 1 1
= − +
12 8(2n + 1) 8(2n + 3)
 
1 1 1
− − + (From (∗2))
12 8[2(m − 1) + 1] 8[2(m − 1) + 3]
1 1 1 1
=− + + −
8(2n + 1) 8(2n + 3) 8(2m − 1) 8(2m + 1)
1 1 (2m + 1) − (2m − 1)
=− + +
8(2n + 1) 8(2n + 3) 8(2m − 1)(2m + 1)
1 1 1
=− + +
8(2n + 1) 8(2n + 3) 4(4m2 − 1)

Take n → ∞ on both sides of the above equation,


∞  
X 1 1 1 1
= lim − + +
(2k − 1)(2k + 1)(2k + 3) n→∞ 8(2n + 1) 8(2n + 3) 4(4m2 − 1)
k=m
1 1 1 1 1
=− lim + lim + (All limits exist.)
8 n→∞ 2n + 1 8 n→∞ 2n + 3 4(4m2 − 1)
1 1 1
=− ·0+ ·0+
8 8 4(4m2 − 1)
1
=
4(4m2 − 1)

The required value of m is given by



X 1 1
>
(2k − 1)(2k + 1)(2k + 3) 4000
k=m
1 1
⇐⇒ >
4(4m2 − 1) 4000
⇐⇒ 1000 > 4m2 − 1 (4m2 − 1 > 0 for all positive integers m)
1001
⇐⇒ m2 <
√4
1001
⇐⇒ m< (m > 1)
2
≈ 15.81929202 . . .

–3–
By Hinyu & Other Minians at Miniforum
Suggested Solution for 2009 Pure Mathematics Paper 1 2nd Edition, last updated at 00:42 on 8 October 2009


X 1 1
∴ The greatest positive integer m such that > is 15.
(2k − 1)(2k + 1)(2k + 3) 4000
k=m

–4–